2021
DOI: 10.1021/acsnano.1c03824
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chirality from Hierarchical Self-Assembly of Atomically Precise Silver Nanoclusters Induced by Secondary Metal Coordination

Abstract: Chiral assembly of metal nanoparticles (NPs) into complex superstructures has been widely studied, but their formation mechanisms still remain mysterious due to the lack of precise structural information from the metal–organic interface to metallic kernel. As “molecular models” of metal NPs, atomically precise metal nanoclusters (NCs) used in the assembly of a macroscale superstructure will provide details of microscopic structure for deep understanding of such highly sophisticated assemblies; however, chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…The variation of the CD spectra after drying indicated that the evaporation of the solvent (water in this case) has an obvious influence on the chirality of the sample, which is reminiscent of the evaporation‐induced changes of the supramolecular chirality of Ag 9 ‐NCs/Ba 2+ hybrid. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation of the CD spectra after drying indicated that the evaporation of the solvent (water in this case) has an obvious influence on the chirality of the sample, which is reminiscent of the evaporation‐induced changes of the supramolecular chirality of Ag 9 ‐NCs/Ba 2+ hybrid. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%
“…We realized that the CD spectra in the current case have good repeatability, which is in sharp contrast to the uncontrollable data observed in systems where supramolecular chirality is dominant. [ 36,39 ] Examinations on the long‐range order of the crystals from Ag 9 ‐NCs/ l ‐TrA hybrid by small‐angle X‐ray scattering (SAXS) measurements (Figure S8, Supporting Information) showed that the scattering pattern is quite similar to those of Ag 9 ‐NCs‐based hydrogel or precipitates induced by achiral organic or inorganic acids where the CD spectra were also found to be uncontrollable (Figure S9, Supporting Information). [ 40,45 ] These observations indicated that the well‐resolved CD signals of the Ag 9 ‐NCs/TrA cocrystals are unlikely from the supramolecular chirality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis, purification and detailed characterization of Ag 9 -NCs can be found in literature [ 6 , 25 ]. DD-5 was purchased from GL Biochem Ltd. (Shanghai, China) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…This study revealed that the ligands’ regiospecific distribution and arrangement formed the anisotropic growth. A very recent study reported the formation of chiral assembly from achiral, atomically precise Ag 9 NCs [ 105 ]. Here, a second metal ion, Ba 2+ , facilitated the assembly process, and thus nanotubes with chiral cubic lattice were obtained.…”
Section: Guided Assembly By External Factorsmentioning
confidence: 99%